2015
DOI: 10.1007/s00281-015-0482-8
|View full text |Cite
|
Sign up to set email alerts
|

Effector CD8 T cell immunity in microsporidial infection: a lone defense mechanism

Abstract: Microsporidia are a group of pathogens, which can pose severe risks to the immunocompromised population such as HIV infected individuals. The expertise to diagnose these pathogens is limited and therefore their prevalence is believed to be much higher than what is currently known. In a mouse model of infections, it has been reported that CD8 T cells are the primary effector cells responsible for protecting the infected host. As the infection is acquired via per-oral route, CD8 T cells in the gut compartment ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Moreover, infection with some microsporidia is a serious threat to human life and health [ 9 , 10 , 11 ]. Although there are many studies on microsporidia, there has not been sufficient research on host response because of the complexity of host–pathogen interactions and the differences among species [ 12 , 13 , 14 ]. The microsporidian N. bombycis was identified from the silkworm, Bombyx mori , in which it causes pebrine and leads to enormous economic losses in the silkworm industry [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, infection with some microsporidia is a serious threat to human life and health [ 9 , 10 , 11 ]. Although there are many studies on microsporidia, there has not been sufficient research on host response because of the complexity of host–pathogen interactions and the differences among species [ 12 , 13 , 14 ]. The microsporidian N. bombycis was identified from the silkworm, Bombyx mori , in which it causes pebrine and leads to enormous economic losses in the silkworm industry [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…We further analyzed the quality of the stimulated antigen-specific T cell responses by evaluating their capacity to produce more than one cytokine, as it was shown that multifunctional T cells are associated with enhanced protection against certain infections. [30][31][32][33] Immunization via the i.n. route using OVA + c-di-AMP alone or in combination with either of the polyphosphazenes efficiently stimulated multifunctional CD4+ T cells (Figure 4 CD4+ T cells, these formulations performed not only better than the formulations incorporating poly I:C but also better than OVA + c-di-AMP alone (7% bi-and 0% trifunctional; P<0.05) (Figure 4, B).…”
Section: Discussionmentioning
confidence: 99%
“…It is well demonstrated that the immune response is important to control the opportunistic Microsporidia infections. The immature and suppressive status of immune systems is a risk factor for microsporidiosis [1][2][3][4]18]. Therefore, younger dogs are at high risk due to their immature immune systems [19,20].…”
mentioning
confidence: 99%
“…We did not evaluate the sanitary management and environmental condition in each facility. However, the reinfection and/or the reactivation of microsporidiosis according to the concentrated environmental contamination by E. bieneusi spores and the frequent close contact with other dogs in the limited space, which is a stressful situation for animals and can induce the immunosuppressive status, are likely to be major causes of high levels of infection in some facilities [4,17,18,21,22]. The results of the present study suggest that there is no correlation between E. bieneusi infection and fecal condition disorder (soft or diarrhea).…”
mentioning
confidence: 99%
See 1 more Smart Citation